Treehouse: A Case For Carbon-Aware Datacenter Software - Anderson, Thomas; Belay, Adam; Chowdhury, Mosharaf; Cidon, Asaf; Zhang, Irene (Workshop on Sustainable Computer Systems Design and Implementation, 2022)
The end of Dennard scaling and the slowing of Moore's Law has put the energy use of datacenters on an unsustainable path. Datacenters are already a significant fraction of worldwide electricity use, with application demand scaling at a rapid rate. We argue that substantial reductions in the carbon intensity of datacenter computing are possible with a software-centric approach: by making energy and carbon visible to application developers on a fine-grained basis, by modifying system APIs to make it possible to make informed trade offs between performance and carbon emissions, and by raising the level of application programming to allow for flexible use of more energy efficient means of compute and storage. We also lay out a research agenda for systems software to reduce the carbon footprint of datacenter computing.